Gold nanoparticles for improved electron microscopic detection of Potato virus M in potato leaves and tubers - Raigond, Baswaraj; A, Jeevalatha; Kumar, Ravinder; Kochhar, Tarvinder; Kaundal, Priyanka; Roach, Shivani; Kumar, Rajender; Singh, B P (Potato Journal, 2016)
The present study was aimed to develop immuno-gold electron microscopic technique to detect Potato virusM (PVM) in potato leaves and tubers. In-house raised antibodies against PVM were used for immuno globulin G (IgG)purification and conjugated with colloidal gold (CG) nanoparticles. The electron microscope (EM) studies revealed thepresence of good concentrations of elongated particles coupled with several IgG conjugated gold (IgG-CG) nanoparticles eithersingle or in small clusters indicating the presence of PVM. The cross reactivity and sensitivity of developed technique wasexamined with the pure cultures of PVY, PVS, PVA, PVX and PVM. Wherein, it revealed that only homologous virus (PVM)was decorated but not the others. The technique was validated with suspected potato leaf samples collected from field. Theresults of the optimized technique were parallel confirmed by RT-PCR wherein, the results supplemented the developedtechnique. The technique was further extended to detect PVM in potato tubers where elongated virus particles coupled withgold nanoparticles were observed revealing the presence of Potato virus M in potato tubers. This study describes a usefulmethod that allows us for same day diagnosis and contributes significantly towards a rapid and clear identification of PVMin potato leaves and tubers.